Attitudinal loyalty, brand value and brand loyalty in the agriculture produce retail industry / Abaidullah Mustaffa - Mustaffa, Abaidullah (2017)
This research analyzed brand loyalty of customers towards hypermarkets or retail stores of agriculture produce. Brand loyalty was studied using attitudinal loyalty and brand value to address the issue of fierce competition among retail stores of agriculture produce. Retaining loyal customers, attracting new customers and moulding them into brand loyal customers could generate accumulative sales growth and volume over time. Attitudinal loyalty comprises of three dimensions: cognitive loyalty, affective loyalty and conative loyalty. Brand value comprises of four component: value, quality, satisfaction and image. Quantitative approach using self-administered questionnaires with 5-point Likert scale was distributed to 420 respondents who were the customers of agriculture produce retailers. Quota sampling design has been chosen because probability sampling criteria cannot be met. Statistical analysis was conducted by SEM using AMOS for structural model that has been tested for reliability and validity leading to hypotheses testing. This study had revealed that attitudinal loyalty has positive effect on brand loyalty and all components of brand value has a positive mediating effect on brand loyalty except value. Value does not mediate positive effect of attitudinal loyalty on brand loyalty. The issue of brand loyalty customers are important in the era of globalization and trade liberalization for repurchase, greater sales, barrier to entry, reduce switching behavior for sustainable business growth.